Fast screening of capacity and internal resistance for cascade utilization of the retired power lithium-ion batteries. (November 2020) - Liu, Weiwei; Li, Honglei; Deng, Yelin; Yang, Fan; Cong, Liang
Abstract: The residual capacity and internal resistance of lithium-ion batteries are important indicators for evaluating the retired batteries, and they are also prerequisites for the cascade utilization of retired batteries. Screening of capacity and internal resistance of retired batteries was studied in this paper. In terms of battery residual capacity, the battery charging system is used to obtain the battery charging curves from which IC characteristics are extracted and screened. The relationship between the IC characteristics and the battery capacity is obtained using a neural network algorithm to achieve capacity estimation. In terms of internal resistance, the charge and discharge strategies of batteries connected in series was first studied, and then a screening method for battery internal resistance was designed based on such charge and discharge strategies. The overall results of this paper provided the basis for the selection of retired power batteries.